Implementing Personal Devices in Math - Jamie W McDaniel (Networks: An Online Journal for Teacher Research, 2020)
This study examined the effect of implementing personal devices into a fifth grade mathematics classroom. Thirty-eight fifth graders participated in this eight-week project with a focus on six students to track their growth. During the study, students engaged in technology based stations that pertained to our geometry unit and coordinate unit. Students took pre and post test on paper to track progress. In addition, students completed online assessments within their practice websites and apps to track comprehension and growth of the content. Furthermore, students were interviewed to ensure they were staying engaged in the online activities and to track student engagement about using personal devices within math.
Keywords: Personal Devices; Math; Technology